Helicobacter pylori induces somatic mutations in TP53 via overexpression of CHAC1 in infected gastric epithelial cells. Issue 4 (9th March 2018) - Wada, Yuriko; Takemura, Kosuke; Tummala, Padmaja; Uchida, Keisuke; Kitagaki, Keisuke; Furukawa, Asuka; Ishige, Yuuki; Ito, Takashi; Hara, Yukichi; Suzuki, Takashige; Mimuro, Hitomi; Board, Philip G.; et al.
Abstract : Infection with Helicobacter pylori is known to decrease the level of glutathione in gastric epithelial cells and increase the production of reactive oxygen species (ROS), which can lead to DNA damage and the development of gastric cancer. Cation transport regulator 1 (CHAC1) has γ‐glutamylcyclotransferase activity that degrades glutathione. We found that cagA ‐positive H. pylori infection triggered CHAC1 overexpression in human gastric epithelial (AGS) cells leading to glutathione degradation and the accumulation of ROS. Nucleotide alterations in the TP53 tumour suppressor gene were induced in AGS cells overexpressing CHAC1, whereas no mutations were detected in cells overexpressing a catalytically inactive mutant of CHAC1. A high frequency of TP53 mutations occurred in H. pylori ‐infected AGS cells, but this was prevented in cells transfected with CHAC1 siRNA. These findings indicate that H. pylori ‐mediated CHAC1 overexpression degrades intracellular glutathione, allowing the accumulation of ROS which subsequently causes mutations that could contribute to the development of gastric cancer. Abstract : Infection with Helicobacter pylori ( H. pylori ) is associated with an increased risk of gastric cancer. This study shows that cagA ‐positive H. pylori ‐mediated overexpression of cation transport regulator 1 (CHAC1) causes glutathione depletion and the accumulation of reactive oxygen species that subsequently leads to nucleotide alterations in the DNA of infected cells. Oxidative DNA damage caused by H. pylori ‐induced CHAC1 overexpression in infected gastric epithelial cells may directly contribute to the development of gastric cancer.